Air/Water Interfacial Formation of "Clean" Tiny AuNPs Anchored Densely on CNT Film for Electrocatalytic Alcohol Oxidation. Issue 6 (27th January 2017) - Zhang, Lei; Tao, Yingzhou; Xiao, Peng; Dai, Liwei; Song, Liping; Huang, Youju; Zhang, Jiawei; Kuo, Shiao‐Wei; Chen, Tao
Abstract : Tiny gold nanoparticles without any surfactant are synthesized via air/water interfacial reaction to be anchored in suit on the surfaces of supported carbon nanotubes in high density. The resultant 2D Janus freestanding composite films exhibit efficient electrocatalytic ability for alcohol oxidation, mainly due to abundant active sites and facile electron transfer.